Deux soeurs - Krajinovic, Jasna (Belgium : C.B.A., Citizen Television, 2005)
Ten years after the end of the war in Kosovo, the wounds are still visible and the ground is still full of landmines. “Two Sisters” is a film about two women’s courageous and determined fight against landmines and their attempts to heal the scars left behind by the war.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films